EphrinA2 regulates clathrin mediated KSHV endocytosis in fibroblast cells by coordinating integrin-associated signaling and c-Cbl directed polyubiquitination. - Dipanjan Dutta (Public Library of Science (PLoS), 2013)
Kaposi's sarcoma-associated herpesvirus (KSHV) interacts with human dermal endothelial cell surface tyrosine kinase EphrinA2 (EphA2) and integrins (α3β1 and αVβ3) in the lipid raft (LR) region, and EphA2 regulates macropinocytic virus entry by coordinating integrin-c-Cbl associated signaling. In contrast, KSHV enters human foreskin fibroblast (HFF) cells by LR-independent clathrin mediated endocytosis. The present studies conducted to identify the key molecules regulating KSHV entry in HFF cells showed that KSHV induces association with integrins (αVβ5, αVβ3 and α3β1) and EphA2 in non-LR regions early during infection and activates EphA2, which in turn associates with phosphorylated c-Cbl, myosin IIA, FAK, Src, and PI3-K, as well as clathrin and its adaptor AP2 and effector Epsin-15 proteins. EphA2 knockdown significantly reduced these signal inductions, virus internalization and gene expression. c-Cbl knockdown ablated the c-Cbl mediated K63 type polyubiquitination of EphA2 and clathrin association with EphA2 and KSHV. Mutations in EphA2's tyrosine kinase domain (TKD) or sterile alpha motif (SAM) abolished its interaction with c-Cbl. Mutations in tyrosine kinase binding (TKB) or RING finger (RF) domains of c-Cbl resulted in very poor association of c-Cbl with EphA2 and decreased EphA2 polyubiquitination. These studies demonstrated the contributions of these domains in EphA2 and c-Cbl association, EphA2 polyubiquitination and virus-EphA2 internalization. Collectively, these results revealed for the first time that EphA2 influences the tyrosine phosphorylation of clathrin, the role of EphA2 in clathrin mediated endocytosis of a virus, and c-Cbl mediated EphA2 polyubiquitination directing KSHV entry in HFF cells via coordinated signal induction and progression of endocytic events, all of which suggest that targeting EphA2 and c-Cbl could block KSHV entry and infection.